Depression among Elderly Residing in Old-age Homes in Devghat, Nepal - Lamichhane, Prava; Nepal, Shobhana; Dhakal, Keshav (Nepal Journal of Health Sciences, 2022)
Introduction: Depression among the elderly is a common phenomenon that is increasing at an alarming rate in recent years. Depression among the elderly leads to various physical and psychological problems and consequently poor quality of life.Objective: This study was aimed at assessing the prevalence of depression among elderly residing in old-age homes in Devghat, Tanahun, Nepal.Methods: A cross-sectional analytical study design was adopted to assess depression among elderly residing in old-age homes of Devghat town in Tanahun district of Nepal. Non-probability enumeration sampling technique was used to collect the data. The validated Nepali translation of the Geriatric Depression Scale-15 was used to assess depression. Collected data were entered in SPSS version 22 and analyzed by using the Chi-square test.Results: Out of 155 respondents, 45.8% had mild depression followed by 36.8% who had moderate depression. A statistically significant association was found between the level of depression and marital status, educational status, asthma, and habit of smoking.Conclusions: This study showed that the prevalence of depression in old-age homes was very high. This necessitates the provision of regular screening and adequate support and initiatives from concerned authorities to uplift the mental status of these elderly people so that it does not affect their overall health and quality of life.